Biotoxic of Gemor (Nothaphoebe coriacea) Leaves from Peat Swamp Tumbang Nusa Research Forest, Central Kalimantan, Indonesia - Iskandar Thalib; Purwanto Budi Santosa; Eko Suhartono (Fakultas Kedokteran Universitas Lambung Mangkurat, 2018)
Abstract: The study aimed to evaluate the sub-acute toxicity effect of aqueous N. coriacea leaves extract to kidney and liver function. The biotoxic study was conducted using male rats. In this study, the experimental animals received five different doses of aqueous N. coriacea leaves extract (0.1 mg, 1 mg, 10 mg, 100 mg, and 1000 mg per day) for 4 weeks via oral route. After treatment, the level of plasma ureum, creatinine, Aspartate Transaminase (AST) and Alanine Transaminase (ALT) level were measured. The results show that most of dose treatments of aqueous extract of N. coriacea leaves had not statistically effect on the level of the plasma ureum and creatinine except for dosage of 1000 mg. Similarly, the dose treatments of that extract did not statistically change the plasma AST and ALT, except on 100 and 1000 mg/kg of b.w extract dose. In conclusion, a short-term intake of N. coriacea leaves extract via oral route was not toxic to kidney and liver. Keywords: N. coriacea, Kidney, Liver, Toxicity.